Exploring AI-mediated Informal Digital Learning of English (AI-IDLE) and its Association with Vocabulary Knowledge among Saudi EFL Learners - AbaAlkhail, Alaa M.; Aljebreen, Saad (Journal of English Language Teaching and Applied Linguistics, 2025)
This study examines the relationship between artificial intelligence-mediated informal digital learning of English (AI-IDLE) on Saudi English as a foreign language (EFL) learners' vocabulary knowledge. With advancements in digital infrastructure in Saudi Arabia, students increasingly turn to digital tools and AI technology to develop language skills autonomously. Despite this shift, research on how Saudi EFL learners utilize AI for vocabulary learning outside the classroom remains limited. This qualitative correlational study examines the relationship between AI-IDLE practices and vocabulary knowledge among Saudi EFL learners, using quantitative data from a survey and vocabulary test (Oxford Online Placement Test). The findings reveled a statistically significant positive correlation between AI-IDLE engagement and vocabulary proficiency. Further analyses indicated that ChatGPT usage significantly predicted vocabulary knowledge, while other AI-tools showed no significant effects. While AI tools were mainly used for translation and writing, indirect vocabulary exposure through AI tools usage supported vocabulary development. Overall, the study offers objective evidence of the contribution of AI-mediated informal digital learning of English to vocabulary knowledge and highlights the pedagogical potential of AI tools beyond traditional classroom settings.